ANALISIS ALOKASI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI DALAM UPAYA PENGEMBANGAN AGRIBISNIS LIDAH BUAYA DI KOTA PONTIANAK - SAFWAN, MULYADI; MUANI, ANI; SUYATNO, ADI (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
This research to be held at North Pontianak district of Pontianak City, used survey method. The aimed of the research are knews to analysis the impact of production factors to the total product and to analysis of the effisiensy using of the production factors Aloe vera farming in the Pontianak City. Colecting the primery data to the all responden as total 43. To analys of the used production factors by function of Cobbs-Douglas production estimates with change in linier function. To knows the impact all of variables independent (Xi) versus variable dependent (Y), used F Test in 95 % significantly and the impact are independent variables (Xi) to variable dependent (Y) used t Test. Effisiency to the production factors used to be analysed by allocative efficiency and use product marginal ratio value similarly with the input cost. The result of the research saw the impact factors of the production seedling, dust, urea are higly significant, exept the labour factor is not significant to the Aloe vera production at center production north Pontianak district of the Pontianak City. The result of the allocative efficiency analysis saw that using the input production seedling, dust and urea in Aloe vera farming are not efficient yet, so need add the input to got allocative efficiency. But labour as an input production is not efficient, and must be lessened to get allocative efficiency. The result of Allocative efficiency economic analysis can be used as adjustment to improve the Aloe vera agribisnis system in Pontianak City.